Desenvolvendo competência em informação na educação profissional e tecnológica por meio da educação on-line : estudo de caso no Instituto Federal de Sergipe - Santos Júnior, Maurício dos (2021)
The present investigation had as objective to implement an online course to train users of the Federal Institute of Sergipe library, Campus Aracaju, enrolled in the subsequent technical course in Electrotechnics, in the development of Information literacy in the context of Professional Education and Technology. Therefore, firstly, the informational needs of the students were identified, in order to establish a dialogue between information literacy, Professional Education and Technology and the Librarian in the mediation of information through online education. From a methodological point of view, an exploratory-descriptive study was carried out, through a Case Study in the library of the IFS/Campus Aracaju, with the universe and sample of Professional Education and Technology students. The approach used was quantitative and quantitative, when, respectively, simple descriptive statistics and Bardin's Content Analysis were used. As for the results, it was concluded that online training, offered by the library, can bring satisfactory results for the development of information literacy skills in Professional Education and Technology students, as the analysis of the participants' perceptions show that the course provided the improvement of skills to carry out efficient searches, mainly through the discovery of more advanced search strategies.